Experimental Results Of Foreign Language Classes Conducted With Students In The Field Of Sports - Muazzamxon Maxammadismoil qizi (Genius Journals, 2025)
This paper analyzes the experience of teaching foreign languages to students majoring in sports using modern methodologies. Experimental sessions were conducted in two groups (experimental and control). The results demonstrate the effectiveness of communicative and contextual approaches in enhancing the foreign language proficiency of sports students
Keywords: sports education; foreign language teaching; communicative method